Virtual Reality - Saied Mashayekh Faridani (صفه)
"Virtual Reality", in the past few years, has turned out to become a well known phenomenon in the scientific world and it seems that it would soon find its true place in the architectural society as well. The present article aims to introduce this new phenomenon to the readers.